Numerical Analysis of Stress Fields Generated in the Gantry Crane Beam. (2017) - Sowa, Leszek; Kwiatoń, Paweł
Abstract: The cranes are currently one of the most common devices for transporting loads and can be applied in many industry areas. This paper includes the numerical strength analysis only of the gantry crane beam. The mathematical model and numerical simulations of mechanical phenomena in the gantry crane beam are presented in this paper. The problem was solved by the finite element method. Analysis was made to the gantry crane beam, which cross-section was the I-beam or T-beam and it was loaded different loads. One takes into consideration in the numerical model the motion of the crane trolley along the beam. As a result of the computations carried out, the stresses and displacements of the structure of gantry crane were obtained. The influences of shape change of the crane beam on the Huber-Mises stress in the steel beam were estimated. It sought to that the maximum value of Huber-Mises stress induced in the gantry crane beam was less than the strength of material, because then the design is safe.